Selection of the solvent and extraction conditions for maximum recovery of antioxidant phenolic compounds from coffee silverskin - Ballesteros, Lina F. (2014)
The extraction of antioxidant phenolic compounds from coffee silverskin (CS) was studied. Firstly, the effect of different solvents (methanol, ethanol, acetone, and distilled water) on the production of antioxidant extracts was evaluated. All the extracts showed antioxidant activity (FRAP and DPPH assays), but those obtained with methanol and ethanol had significantly higher (p < 0.05) DPPH inhibition than the remaining ones. Due to the lower toxicity, ethanol was selected as extraction solvent, and further experiments were performed in order to define the solvent concentration, solvent/solid ratio, and time to maximize the extraction results. The best condition to produce an extract with high content of phenolic compounds (13 mg gallic acid equivalents/g CS) and antioxidant activity [DPPH = 18.24 μmol Trolox equivalents/g CS and FRAP = 0.83 mmol Fe(II)/g CS] was achieved when using 60 % ethanol in a ratio of 35 ml/g CS, during 30 min at 60–65 °C.